Polymeric Micelle as a New Carrier in Oral Drug Delivery Systems - Esfahani, Golbarg (Asian Journal of Pharmaceutics (AJP), 2018)
Almost half of the orally administered drugs are poorly soluble in water; therefore they have low absorption in the gastrointestinal (GI) tract. In addition, drugs which are administered orally must remain stable during passing the GI tract, despite different physiologic challenges such as pH changes, and dilution effect. Hence, new methods are needed to increase the solubility of these drugs while making them more stable in the physiologic environment. Polymeric micelles are one of the new nanocarriers which are able to increase the solubility of these drugs while protecting them from pH changes, dilution effect, and biological barriers such as filtration in the spleen or scavenging by the phagocytic system. This article provides some important and basic information including polymeric micelles characteristics, structure, and preparation.